Development Strategy of Teacher Competence with the 70-20-10 Model for SDG-Aligned Community-Based Education: A Literature Review - Enung Hasanah; M Ikhsan Al Ghazi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2025)
Education plays a vital role in shaping the development of society and the nation. In a rapidly changing world, teachers are key players in preparing the next generation to face increasingly complex challenges. Within this dynamic context, improving teacher competencies has become a critical need. One alternative approach is the 70-20-10 Model, which combines formal learning, informal learning, and learning through experience, while also integrating community-based learning, and social engagement to support the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) and SDG 17 (Partnerships for the Goals). This paper explores the key principles of the 70-20-10 Model in the context of teacher professional development and its potential to encourage local and global collaboration for achieving inclusive, equitable, and sustainable education outcomes. Through a comprehensive literature review, this study discusses the implications, benefits, and challenges related to the implementation of this model. The findings highlight that the 70-20-10 Model provides a solid framework for continuous teacher development, where 10% of learning comes from structured activities such as workshops or training sessions, 20% from collaborative learning through interactions with peers and mentors (both online and offline), and 70% from practical classroom experience integrated with community involvement. However, the implementation of this model also faces several challenges, including limited resources, resistance to change, and difficulties in measuring learning outcomes. Therefore, to fully realize the potential of this model, strong commitment from all stakeholders is needed, along with supportive systems and well-planned strategies that are responsive to both local contexts and global education priorities.